رقابة قضاء المظالم على أعمال الإدارة في المملكة العربية السعودية = Grievances judiciary supervision of administrative works in Saudi Arabia and differentiating it from the grievances judiciary supervision in the Islamic law - Alyahya, Sultan Hassan; Ibrahim, Badruddin; Laeba, Muhammad (International Islamic University Malaysia, 2016)
Jurists of administrative law consider judicial Supervision of administrative works and their actions one of the means of preserving the principle of legitimacy, which the principle that preserves the rights of individuals as well as the organization’s stability. In this context, this study attempts to shed light upon the applied general principles through which the Bureau of Grievances in the Kingdom of Saudi Arabia exercises its Supervision of management activities reflected by the implementation of the systems and rules and operating public facilities. This will be accomplished through a demonstration of the tasks of administrative courts that work under the Bureau of Grievances in its three sections: the supreme administrative court, administrative courts of appeal, and administrative courts (courts of first instance), followed by a highlight of the limits of loyalty scope of the Supervision of the Saudi administrative judiciary of administrative activities. This method will be followed by an attempt to explain texts and revealing the vague ones and benefiting from the judicial rules as practical instances. The study concludes by illustrating cases the researcher believes to be more important for differentiating grievances judiciary in Islamic system from grievances of judiciary in the Saudi system. The study is concluded by a conclusion that summarizes the research and furnishes some suggestions about its findings.